1987
DOI: 10.1177/004051758705701005
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Wool Carbonizing

Abstract: The surface barrier effect in dyeing carbonized wools was examined by dyeing various carbonized wools with CI acid red 1 at 25°C. Free acid is more evenly distributed on the surface of the wool fibers in rapid carbonizing than in conventional carbonizing. This free acid sulfates the surface layer of the wool during rapid carbonizing without increasing the permeability of the cuticle layer to dye. The distribution of the bound

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…A 10 min time delay was found to be the optimum for both minimum damage and industrial productivity [60]. The delay was also found to have an effect on the dyeing properties of rapidly carbonised wool [61].…”
Section: Ll Flgure 1 Spindle-like Acid Droplet On a Wool Fibre (Repromentioning
confidence: 91%
See 1 more Smart Citation
“…A 10 min time delay was found to be the optimum for both minimum damage and industrial productivity [60]. The delay was also found to have an effect on the dyeing properties of rapidly carbonised wool [61].…”
Section: Ll Flgure 1 Spindle-like Acid Droplet On a Wool Fibre (Repromentioning
confidence: 91%
“…Zhao and Pailthorpe have studied the surface barrier effects produced in rapidly carbonised wool and found that rapid carbonising also introduces a dye-resist effect into the carbonised wool [61]. In addition, it was found that the free acid is more evenly distributed on the surface of the fibres and in the surface layer in rapid carbonising, as compared with conventional carbonising.…”
Section: Effects Of Sulphuric Acid On Woolmentioning
confidence: 99%